Development of Gimkit Media in Learning Pancasila Education in Grade VI Elementary School - Putri Amelya Ruli Permata Dewi (Jurnal Gentala Pendidikan Dasar, 2025)
The Pancasila Education subject plays a crucial role in shaping students character from an early age. However, students interest in the subject tends to be low due to conventional and monotonous learning methods. This study aims to develop an educational game-based learning media using the Gimkit platform to enhance the teaching of Pancasila Education in Grade VI of elementary school. The research employed a R&D approach with the ADDIE model. The validation results from media, material, and language experts showed that the media was highly valid, with scores of 86%, 96%, and 90%, respectively. Implementation involved 12 sixth-grade students at UPT SDN Kedungjambe 1. The practicality test based on teacher and student responses yielded percentages of 92% and 95.4%, respectively, categorized as very practical. Furthermore, the effectiveness was evaluated using pre-test and post-test results, with an average gain score of 0.8, indicating high effectiveness. This shows that the Gimkit-based learning media is valid, practical, and effective. Therefore, this media is recommended as an innovative alternative to support the implementation of the independent curriculum in elementary schools.